The 2S2P1D - An Excellent Linear Viscoelastic Model - M.D, Yusoff; N.I, Monieur; G.D, Airey (Universiti Malaysia Sarawak, (UNIMAS), 2010)
An experimental campaign has been carried out on five different unaged and five aged penetration grade bitumens to determine the properties of the 2S2P1D (combinations of two springs, two parabolic elements and one dashpot) model. The dynamic oscillatory test was conducted in order to obtain the rheological data using the dynamic shear rheomater (DSR)